IMPLEMENTATION OF THE DIGITAL POPULATION IDENTITY (IKD) APPLICATION AS AN INNOVATION IN POPULATION ADMINISTRATION SERVICES IN LARANGAN VILLAGE - Pravitasari, Novalia Eka; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Digital Population Identity (IKD) application as an innovation in population administration services in Larangan Village, Candi District, Sidoarjo Regency. Method: A qualitative research approach was employed, with data collected through interviews, observations, and documentation, and analyzed using George C. Edward III’s policy implementation theory, which emphasizes communication, resources, disposition, and bureaucratic structure. Results: The findings reveal that the implementation of IKD in Larangan Village is not yet optimal. Communication is hindered by uneven information dissemination, unclear messages, and inconsistent coordination across implementing levels. Resource constraints remain significant, including limited human resources, insufficient technical competence, inadequate infrastructure, and budgetary shortcomings. The disposition of implementers indicates acceptance but lacks proactive commitment, while the bureaucratic structure is weakened by the absence of specific standard operating procedures (SOPs) and regular monitoring mechanisms. Novelty: This study contributes to the literature by providing empirical insights into the early-stage challenges of digitizing population administration at the village level, highlighting the need for structured socialization, capacity building, and regulatory reinforcement to achieve effective and sustainable digital service innovation.